Incidence and probable risk factors of post COVID syndrome among COVID-19 patients in urban population of North Kerala: a 6 months cohort study - K. R., Deepa; Mohandas, Bindu; Thayyil, Jayakrishnan; Nair, Meera S.; P., Rosh; Kumar, Durgesh (International Journal Of Community Medicine And Public Health, 2023)
Background: Post-COVID condition is an important health burden all over world. This study was conducted to determine incidence, symptoms and risk factors of post COVID syndrome. Methods: Cohort study was done on COVID-19 patients of Mukkam Municipality tested from Mukkam Community Health Centre. Baseline data was collected using pre-tested semi-structured questionnaire by direct interview method after obtaining their consent. Subjects were followed up weekly for 6 months to know occurrence of post COVID syndrome, its course and outcome if any. Incidence and relative risk for age, gender, COVID-19 vaccination status, comorbidities and severity of COVID-19 illness were assessed for post COVID syndrome. Chi-square test was used for statistical association between severity of COVID-19 and occurrence of post COVID syndrome. Results: Among 800 persons tested for COVID-19, 28.75% were tested positive. Incidence of post COVID syndrome among study subjects was 42.2%. Relative risk for post COVID was high among participants having age more than 60 years (RR-1.76), females (RR-1.07), with comorbidities like diabetes (RR-1.28), hypertension (RR-1.06) and cardiac illness (RR-1.05), unvaccinated status (RR-1.21) and in severe COVID-19 infection (1.20). There is a significant statistical association between occurrence of post COVID syndrome and degree of severity of COVID-19 disease (p=0.0046). Conclusions: Post-COVID syndrome was found more often in older people who had severe COVID-19 illness, also incidence increases with severe COVID-19 illness.